Estimation the Levels of Some Inflammatory Markers Among Young Iraqi Smokers and Non Smokers - G. AL- Suhail, Raghad (Iraqi Journal of Science, 2023)
In this study it was found that a significant decrease in the level of leptin in youngIraqi smokers (16+ 0.7ng/mL) compared to non smokers(24.2+ 4.5ng/mL) while, B2microglobulin and CRPwas significantly increased in the smokers (1.2 + 0.3μg/mL),(4.07+ 0.02mg/L) respectively, compared to non smokers (0.6 + 0.9μg/mL) ,( 2.88+0.002mg/L) respectively, the presented data indicates the effect of smoking on theseimmunological markers.